2018
DOI: 10.1083/jcb.201808077
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mitotic therapies in cancer

Abstract: Tischer and Gergely review the cell biology behind microtubule poisons and their clinical use in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 10 publications
0
61
0
Order By: Relevance
“…Since both topoisomerase inhibitors, such as doxorubicin or etoposide, and HDAC inhibitors are known to cause direct or indirect DNA damage, respectively, it is likely they might overcome resistance by potentiating the level of DNA damage in 177 Lu-RIT-targeted cells (2426). Therefore, we focused on the third group of compounds, the mitotic kinase inhibitors, that affect kinases with critical functions for both mitotic entry and exit, and have a role in termination of the DNA damage-induced G 2 -checkpoint (2729). In particular we further explored the combination of 177 Lu-lilotomab satetraxetan with the dual CDK1/2-Aurora A/B inhibitor JNJ-7706621, the Aurora A inhibitor alisertib (MLN8237), and the Plk1 inhibitor GSK461364, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since both topoisomerase inhibitors, such as doxorubicin or etoposide, and HDAC inhibitors are known to cause direct or indirect DNA damage, respectively, it is likely they might overcome resistance by potentiating the level of DNA damage in 177 Lu-RIT-targeted cells (2426). Therefore, we focused on the third group of compounds, the mitotic kinase inhibitors, that affect kinases with critical functions for both mitotic entry and exit, and have a role in termination of the DNA damage-induced G 2 -checkpoint (2729). In particular we further explored the combination of 177 Lu-lilotomab satetraxetan with the dual CDK1/2-Aurora A/B inhibitor JNJ-7706621, the Aurora A inhibitor alisertib (MLN8237), and the Plk1 inhibitor GSK461364, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Aurora kinases are known to play pleiotropic roles during mitosis. They are notably important for the capture, alignment, and segregation of chromosomes and thus were subjects of intensive screening campaign to characterize new potent inhibitors: 50+ clinical trials were performed in solid and hematological tumors [45]. Following the screening of kinases, we showed that P3 decreased the viability of two- and three-dimensional cell cultures and induced apoptosis of U-2 OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study suggest that the canonical centrosomal pathway and the NuMA-mediated acentrosomal pathway complementally regulate bipolar spindle assembly in somatic cells, and that the latter becomes predominant in the absence of centrosomes (Figure 2). Understanding the multiple pathways that ensure robust bipolar spindle formation will assist in the design of anticancer drugs that target spindle assembly (Henriques et al, 2019;Tischer and Gergely, 2019).…”
Section: Chinen Et Al 2020mentioning
confidence: 99%